B33. Immunology/Inflammation 2009
DOI: 10.1164/ajrccm-conference.2009.179.1_meetingabstracts.a2860
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins Regulate Bone Marrow Stromal Cell IL-6 Expression through the MAPK Pathway.

Abstract: Background: The host's response to infection is characterized by altered levels of neurotrophins and an influx of inflammatory cells to sites of injured tissue. Progenitor cells that give rise to the differentiated cellular mediators of inflammation are derived from bone marrow progenitor cells where their development is regulated, in part, by cues from bone marrow stromal cells (BMSC). As such, alteration of BMSC function in response to elevated systemic mediators has the potential to alter their function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Consistent with this hypothesis are the results of Rezaee et al . who reported that neurotrophins stimulate BM stromal cell to secrete IL‐6, a factor recently identified to be involved in myeloma‐induced RANKL expression in T lymphocytes by Giuliani et al . Combined with our previous data that BDNFs are correlated with MIP‐1α, and β2‐microglobulin levels in patients with active myeloma, these data suggest that the complex interaction between BDNF and other OAFs in BM appears to be responsible in part for myeloma bone disease.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with this hypothesis are the results of Rezaee et al . who reported that neurotrophins stimulate BM stromal cell to secrete IL‐6, a factor recently identified to be involved in myeloma‐induced RANKL expression in T lymphocytes by Giuliani et al . Combined with our previous data that BDNFs are correlated with MIP‐1α, and β2‐microglobulin levels in patients with active myeloma, these data suggest that the complex interaction between BDNF and other OAFs in BM appears to be responsible in part for myeloma bone disease.…”
Section: Discussionsupporting
confidence: 79%
“…Although mechanisms underlying their regulatory action in osteogenic process have not been completely elucidated, recent studies showed that many mediators of the inflammatory response play a key role in osteogenesis. Among DEG, a set of genes known to be involved both in inflammation and bone formation appears, which includes: IL6, encoding a cytokine that acts in the maturation of B cells, is known to be an important pro-inflammatory cytokine secreted by osteoblasts in bone resorption process [ 73 ], and in human BMSCs it seems to positively influence the mitogen-activated protein kinase signaling cascade, essential for normal skeletogenesis and bone formation [ 74 ]; the protein encoded by PTGES gene, a glutathione-dependent prostaglandin E synthase, was evidenced in the monolayered MSCs [ 75 ] and several studies suggest this gene contributing to decrease cell proliferation and induces osteogenesis [ 76 ]; IL1, an heterodimer containing α and β subunits, seems to intervene in bone remodeling process [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…NGF reportedly up‐regulates the expression of adhesion molecules and stimulates the proliferation of endothelial cells (Kolostova et al, ; Raychaudhuri, Raychaudhuri, Weltman, & Farber, ) and the up‐regulated adhesion molecules attract leukocytes into the injury site during the injury repair process. Another in vitro study also demonstrated that adding NGF and BDNF to cultured bone marrow stromal cells increased the expression of the pro‐inflammatory cytokine, IL‐6 (Rezaee et al, ). In a mouse model of ear cartilage injury, pre‐treatment with NGF enhanced the healing process by directly inducing an inflammatory response and indirectly by stimulating angiogenesis (Kolostova et al, ).…”
Section: Potential Roles Of Neurotrophins In Skeletal Tissue Injury Rmentioning
confidence: 98%